Sejarah Perkembangan Tarekat Naqsyabandiyah, Ajaran-ajarannya Zikir, Wirid dan Metodenya - N, Nurbaya; Damis, Rahmi; Harun, Hamzah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines the history of the development of the Naqsyabandiyah order, its teachings, dhikr, wirid and methods. In this manuscript, the process of the development of the Naqsyabandiyah order in Indonesia is discussed and there are several basic teachings of the Naqsyabandiyah order such as huway dardam, nazhar barqadam, safar darwathan, khalwat daranjaman wuquf qalbi and so on as steps to reach the level of makrifatullah. Zikir is an effort to remember Allah by saying the name of Allah to achieve human awareness of his position, zikr is a basic practice in the tarekat in which there is silent zikr done in the heart without sound with methods taught by a musryid that vary according to the capacity of his students, the levels of zikr here are mukasyafah saying the name of Allah as much as approximately 5000 in a day, lathaif 6.000 to 11,000, nafi by saying the sentence Laa ilaha illallah, wuquf qalbi is not negligent in zikr, ahdian always remembers Him, even with the remembrance of closeness to Allah wholeheartedly and tahlil which is zikr with a voice based on the determination of a mursyid.